Distressing Belching with Chorea Induced by Caudate Infarction - Yui Sanpei; Akira Hanazono; Sachiko Kamada; Masashiro Sugawara (Case Reports in Neurology, 2021)
Although belching is mostly associated with gastrointestinal disorders, it occasionally accompanies movement disorders such as Parkinsonism or dystonia. A woman in her 80s presented distressing belching and chorea of the right arm and leg from 3 years earlier. A brain MRI showed a left caudate infarction and atrophic change. Haloperidol significantly improved belching and chorea. Caudate infarction can cause distressing belching with chorea. It might be important to select the appropriate drug by referring to the accompanying involuntary movement to treat belching with movement disorders.